Treatable traits can be identified in a severe asthma registry and predict future exacerbations. Issue 1 (19th September 2018) - McDonald, Vanessa M.; Hiles, Sarah A.; Godbout, Krystelle; Harvey, Erin S.; Marks, Guy B.; Hew, Mark; Peters, Matthew; Bardin, Philip G.; Reynolds, Paul N.; Upham, John W.; Baraket, Melissa; Bhikoo, Zaheerodin; et al.
ABSTRACT: Background and objective: A new taxonomic and management approach, termed treatable traits, has been proposed for airway diseases including severe asthma. This study examined whether treatable traits could be identified using registry data and whether particular treatable traits were associated with future exacerbation risk. Methods: The Australasian Severe Asthma Web‐Based Database (SAWD) enrolled 434 participants with severe asthma and a comparison group of 102 participants with non‐severe asthma. Published treatable traits were mapped to registry data fields and their prevalence was described. Participants were characterized at baseline and every 6 months for 24 months. Results: In SAWD, 24 treatable traits were identified in three domains: pulmonary, extrapulmonary and behavioural/risk factors. Patients with severe asthma expressed more pulmonary and extrapulmonary treatable traits than non‐severe asthma. Allergic sensitization, upper‐airway disease, airflow limitation, eosinophilic inflammation and frequent exacerbations were common in severe asthma. Ten traits predicted exacerbation risk; among the strongest were being prone to exacerbations, depression, inhaler device polypharmacy, vocal cord dysfunction and obstructive sleep apnoea. Conclusion: Treatable traits can be assessed using a severe asthma registry. In severe asthma, patients express more treatable traits than non‐severe asthma. Traits may be associated with future asthma exacerbation risk demonstrating the clinical utility of assessing treatable traits. Abstract : We assessed the prevalence of treatable traits in severe asthma compared with non‐severe asthma, and assessed the relationship between treatable traits and future exacerbation risk. We demonstrate the usefulness of the treatable traits approach in severe asthma and which specific treatable traits are predictive of future asthma attacks. See related Editorial